2002
DOI: 10.7326/0003-4819-137-8-200210150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Ximelagatran versus Warfarin for the Prevention of Venous Thromboembolism after Total Knee Arthroplasty

Abstract: For prophylaxis of venous thromboembolism, fixed-dose ximelagatran started the morning after total knee arthroplasty is well tolerated and at least as effective as warfarin, but it does not require coagulation monitoring or dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(102 citation statements)
references
References 27 publications
1
99
0
2
Order By: Relevance
“…Three randomized controlled trials satisfying the inclusion criteria were identified. [13][14][15] No articles were excluded. All studies gave details concerning the method used to detect VTE as well as defi nitions of clinical and laboratory outcomes, which were comparable between trials.…”
Section: Literature Search Results Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three randomized controlled trials satisfying the inclusion criteria were identified. [13][14][15] No articles were excluded. All studies gave details concerning the method used to detect VTE as well as defi nitions of clinical and laboratory outcomes, which were comparable between trials.…”
Section: Literature Search Results Literature Search Resultsmentioning
confidence: 99%
“…They were conducted in 115 13 15 The orthopedic surgery performed was knee replacement in two studies 13,14 and knee arthroplasty in one study. 15 Drug administration was oral in all groups.…”
Section: Characteristics Of Included Characteristics Of Included Studmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, seven to 12 days of fixed-dose ximelagatran 24 mg twice daily was at least as effective as warfarin, both regimens being initiated the morning after TKR. 45 In the second study, ximelagatran at a dose of 36 mg twice-daily for seven to 12 days was more effective than warfarin regarding the primary composite endpoint defined as total DVT, PE and death from all causes (20.3 vs 27.6%). Rates of bleeding were similar between the two groups.…”
Section: Direct Thrombin Inhibitorsmentioning
confidence: 96%